Pengaruh Pemberian Video Edukasi Sikat Gigi (VIDUS) terhadap Tingkat Pengetahuan Kebersihan Gigi pada Anak di SD Negeri 26 Pemecutan - Ni Putu Eka Dina Lestari Putri; Komang Yogi Triana; Ni Komang Purwaningsih; I Wayan Darsana (Jurnal Ilmiah Kesehatan Pernus, 2025)
Oral health is important, especially for children, because dental problems can cause pain and difficulty chewing. Dental and oral health can significantly impact general health, especially children’s growth and development. The prevalence of dental caries has increased due to children’s lack of interest in and comprehension of correct toothbrushing techniques. Interesting educational methods, such as animated videos, are needed to increase children’s dental hygiene knowledge. This study aimed to determine the effect of providing toothbrush educational video on the knowledge level of students’ dental hygiene at SD Negeri 26 Pemecutan. This study was a quantitative study that employed a pre-experimental procedure with a one-group pretest-posttest design. Samples were taken using a total sampling technique yielded 85 samples. The research instrument was a questionnaire about dental hygiene knowledge. The data were analyzed using univariate and bivariate Paired T-Tests. Based on the results of the bivariate test research, the average pre-test value was 9.98, while the post-test value was 13.61, with a P value of 0.001, implying that the toothbrush educational video had an impact on the knowledge level of students’ dental hygiene at SD Negeri 26 Pemecutan. It is expected that students at SD Negeri 26 Pemecutan will retain the knowledge provided on brushing their teeth and implement it in everyday life.